2018
DOI: 10.1007/s10549-018-4880-1
|View full text |Cite
|
Sign up to set email alerts
|

Onco-metabolism: defining the prognostic significance of obesity and diabetes in women with brain metastases from breast cancer

Abstract: Elevated BMI or diabetes may negatively impact both overall survival and local control in patients with brain metastases from breast cancer, highlighting the importance of the translational development of therapeutic metabolic interventions. Given its prognostic significance, BMI should be used as a stratification in future clinical trial design in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…We defined patients with Ki-67 expression above the cutoff point as the Ki-67 high group, otherwise as the Ki-67 low group. Propensity score matching 11 (PSM, ratio = 1:2) was performed to match the patients in the Ki-67 low group with those in the Ki-67 high group to balance baseline characteristics and potential prognostic confounders [12][13][14] , including age, BMI, location, T-stage, multifocality and N-stage. The chi-square test for categorical variables was used for comparisons between groups.…”
Section: Discussionmentioning
confidence: 99%
“…We defined patients with Ki-67 expression above the cutoff point as the Ki-67 high group, otherwise as the Ki-67 low group. Propensity score matching 11 (PSM, ratio = 1:2) was performed to match the patients in the Ki-67 low group with those in the Ki-67 high group to balance baseline characteristics and potential prognostic confounders [12][13][14] , including age, BMI, location, T-stage, multifocality and N-stage. The chi-square test for categorical variables was used for comparisons between groups.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the previous section, the antibiotic vancomycin reduces bacterial-derived SCFAs highlighting an intersection between microbiota and metabolism regulation that it is likely to influence tumor growth and the response to therapy through the PPAR-g pathway. Dr. N. Simone from Thomas Jefferson University presented results from a clinical study showing that patients with diabetes treated with intracranial radiotherapy have reduced overall survival and reduced median intracranial progression-free survival compared with nondiabetic individuals, emphasizing a role of host metabolism in radiotherapy response (25). She discussed results where caloric restriction led to radiosensitization of tumors in preclinical models and also suggested the potential of ketogenic diets, which are low in carbohydrates, to sensitize tumors to radiotherapy.…”
Section: How the Metabolome Affects The Response To Radiationmentioning
confidence: 99%
“…Further, RT reduces the long-term risk for local recurrence [5].Beyond RT, systemic treatments such as endocrine therapy are also a mainstay in BC treatment; however, flexible guidelines and patient preferences often leave therapy choice to physicians' discretion although endocrine therapy is recommended for patients whose cancer display any level of estrogen expression [6,7]. Notably, it has been found that endocrine therapy and RT can be safely concurrently administered without danger of weakening disease control [6].Obesity has been implicated as a risk factor in RT resistance, metastasis, and overall poor prognosis in breast cancer [8][9][10]. Furthermore, moderate to severe obesity increases the likelihood of BC recurrence and BC-specific mortality [10,11].…”
mentioning
confidence: 99%
“…Furthermore, moderate to severe obesity increases the likelihood of BC recurrence and BC-specific mortality [10,11]. Obesity may promote resistance to RT through metabolic dysregulation and altered signaling axis [8]. Women who receive whole breast RT were 12.6% more likely to have regional recurrence after 5 years if they had two or more risk factors for breast cancer, including obesity [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation